2006
DOI: 10.1111/j.1525-1497.2005.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Hospitalized patients’ attitudes about and participation in error prevention

Abstract: BACKGROUND AND OBJECTIVE: Although many patient safety organizations and hospital leaders wish to involve patients in error prevention, it is unknown whether patients will take the recommended actions or whether error prevention involvement affects hospitalization satisfaction. DESIGN AND PARTICIPANTS: Telephone interviews with 2,078 patients discharged from 11 Midwest hospitals. RESULTS: Ninety‐one percent agreed that patients could help prevent errors. Patients were very comfortable asking a medication's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 10 publications
10
103
0
6
Order By: Relevance
“…Other clinical interventions that could potentially reduce the incidence and burden of ADRs include using a preferred prescriber and medication reconciliation interventions that include patient education regarding their medications. [3942]…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical interventions that could potentially reduce the incidence and burden of ADRs include using a preferred prescriber and medication reconciliation interventions that include patient education regarding their medications. [3942]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies showed that the extent to which patients believed that their participation would prevent infections increased their intention to ask clinicians to wash their hands (Abbate et al, 2008;Longtin et al, 2009;Luszczynska & Gunson, 2007). Similarly, feeling more comfortable with error prevention increased willingness to act (Waterman et al, 2006). Extraversion was associated with patients" willingness to ask clinicians, including doctors, to wash their hands (Duncanson & Pearson, 2005;Longtin et al, 2009).…”
Section: Cognitive Factorsmentioning
confidence: 99%
“…The review found evidence that patients were generally willing and able to report formally incidents such as drug complications and medication errors as this did not require the overt questioning of clinicians (Jarernsiripornkul et al, 2002(Jarernsiripornkul et al, , 2003van den Bemt et al, 1999;Waterman et al, 2006;Weingart et al, 2004). However, an important barrier is that generally patients were not made aware of the incident reporting system (Frey et al, 2009;Watt et al, 2009 (Coulter & Ellins, 2006).…”
Section: Organisational Aspectsmentioning
confidence: 99%
See 2 more Smart Citations